1991
DOI: 10.1111/j.1469-8749.1991.tb05111.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative Jejunostomy‐tube Feeding in Reconstructive Spinal Surgery

Abstract: Eight malnourished children with neuromuscular spinal deformity were treated with jejunostomy tubes for supplemental feeding to attain appropriate weight before reconstructive surgery. All patients had significant gastro-esophageal reflux and had failed to gain weight during an eight-month oral supplementation program. There were no complications associated with the placement or use of the jejunostomy feeding tubes and all patients gained weight in a safe and predictable fashion, had successful spinal fusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Patients with CP and NM scoliosis routinely receive a preoperative evaluation by a nutritionist and/or gastroenterologist in preparation for surgery and continue to be followed up postoperatively as appropriate. While many of our patients therefore receive additional caloric intake, leading to weight gain, and research indeed shows that enteric feeding leading up to surgery can improve weight status in preparation for spinal surgery, 9 we did not observe an upward trend in weight percentile over the year prior to surgery in our series. This suggests that the postoperative trends in weight observed in our series should not be simply attributed to nutritional supplementation, and physiological changes after surgery may-at least partly-account for postoperative weight changes in the most vulnerable patients.…”
Section: Discussionmentioning
confidence: 44%
“…Patients with CP and NM scoliosis routinely receive a preoperative evaluation by a nutritionist and/or gastroenterologist in preparation for surgery and continue to be followed up postoperatively as appropriate. While many of our patients therefore receive additional caloric intake, leading to weight gain, and research indeed shows that enteric feeding leading up to surgery can improve weight status in preparation for spinal surgery, 9 we did not observe an upward trend in weight percentile over the year prior to surgery in our series. This suggests that the postoperative trends in weight observed in our series should not be simply attributed to nutritional supplementation, and physiological changes after surgery may-at least partly-account for postoperative weight changes in the most vulnerable patients.…”
Section: Discussionmentioning
confidence: 44%
“…The authors found that children with poor presurgical nutritional status, defined as total blood lymphocyte count (TLC) <1500 cells per cubic millimeter and albumin levels < 3.5 g/dL, were at risk for postsurgical infectious complications, consisting of 11 urinary tract infections, 9 pneumonias, 2 gastrointestinal (GI)/genitourinary infections, and 2 surgical site infections (SSI). These data led to a growing trend for evaluation of presurgical nutritional status and a recommendation for aggressive measures, such as perioperative feeding tube interventions, 21 to be instituted to optimize nutritional levels.…”
Section: General Considerationsmentioning
confidence: 99%